THE FORMING OF CREATIVE PERSONALITY OF FUTURE MUSIC TEACHER DURING THE INDIVIDUAL HOURS - O.V. Laduba (Academy of Cognitive and Natural Sciences, 2022)
The author view! the necessity of reorientation of individual work and turn if from the informative function to personality, to the forming of students personal creative component.